العادات والتقاليد النصرانية في الأندلس في عصر بني الأحمر - سلاطنة,امنة; خضير,فتيحة (University of Eloued جامعة الوادي, 2024)
عمل اللإنسان القوطي على الحفاظ و التمسك بالعادات والتقاليد ، وبعد الفتح الإسلامي للأندلس جدد فيها الحياة وامتزجت حضارات سابقة مع حضارات جديدة لتصنع عادات وتقاليد مشتركة ولا شك أن التمازج الذي حدث بين المسلمين والمسيحيين إبان الحكم الإسلامي للأندلس وبالخصوص في عهد بني الأحمر من خلال الحروب وما نجم عنها من سبى متبادل و اختلاط مباشر إما عن طريق الجواري أو التجارة المتبادلة وكذا التزاوج الذي أدى بدوره إلى خلق بوادر التأثير والتأثر بين عناصر المجتمع الأندلسي في عهد بني الأحمر بالخصوص. ضرب المجتمع الأندلسي في عصر بني الأحمر أروع الأمثلة في التسامح والتعايش المشترك رغم اختلاف الدين والعادات. تأثر الإسباني على العرب من خلال احتفالهم بأعياد جيرانهم المسيحيين, فقد عبرت الاحتفالات التي كانت تقام بالأندلس، عن التعایش المشترك رغما لاختلاف العرقي والدیني ،لم یجد المسلمین إي إحراج في مشاركة إخوانهم المسيحيين مناسبتهم ،رغم تحذير الفقهاء الذین اعتبروا مشاركة مسلمي الأندلس في أعیاد غير المسلمين بدعه. Abstract: The Gothic man worked to preserve and adhere to customs and traditions, and after the Islamic conquest of Andalusia, he renewed life in it and previous civilizations mixed with new civilizations to create common customs and traditions. There is no doubt that the intermingling that occurred between Muslims and Christians during the Islamic rule of Andalusia, especially during the era of Banu al-Ahmar, through wars and the resulting mutual captivity and direct mixing either through concubines or mutual trade, as well as intermarriage, which in turn led to the creation of signs of influence and impact between the elements of Andalusian society during the era of Banu al-Ahmar in particular. Andalusian society in the era of Banu al-Ahmar set the most wonderful examples of tolerance and coexistence despite the difference in religion and customs. The Spanish influenced the Arabs through their celebration of the holidays of their Christian neighbors, as the celebrations that were held in Andalusia expressed coexistence despite the ethnic and religious differences. Muslims did not find any embarrassment in participating with their Christian brothers in their occasions, despite the warnings of jurists who considered the participation of Andalusian Muslims in the holidays of non-Muslims an innovation.
Keywords: Customs and traditions; Goths; Muslims; Christians; Andalusia; العادات والتقاليد; ، المسحيين; ، الاندلس; القوطي